Carbon emission rebound in Indonesia’s post-pandemic recovery: Decoupling dynamics and Islamic economic perspectives on green policy - Hastin, Mira; Putri , Osi Hayuni (Universitas Islam Indonesia, 2026)
IntroductionThe COVID-19 pandemic temporarily weakened the relationship between economic growth and carbon emissions in many countries. In Indonesia, however, the sustainability of this decoupling remains uncertain because the post-pandemic recovery was shaped by fiscal expansion, commodity-driven trade surplus, and continued dependence on carbon-intensive sectors. This issue is especially important because Indonesia is simultaneously pursuing economic recovery, climate commitments, and sustainable development within a Muslim-majority context where Islamic economic ethics can enrich environmental policy analysis.ObjectivesThis study examines whether Indonesia’s post-pandemic economic recovery sustained the temporary decoupling of economic growth from carbon emissions observed in 2020 or instead produced a carbon-emission rebound. It also explores the associations between emission dynamics, government expenditure, and trade balance, while interpreting the findings through Islamic economic principles, including maqasid al-shariah, maslahah, mizan, khalifah, amanah, and the prevention of ecological harm.MethodThis study uses a longitudinal descriptive-diagnostic design based on annual Indonesian data from 2016 to 2024. The analysis combines trend analysis, Tapio decoupling elasticity, Spearman rank correlation, and a simple scale-intensity decomposition. Islamic economics is incorporated as a normative interpretive framework to assess the ethical and policy implications of carbon-intensive recovery.ResultsThe findings show that Indonesia’s pandemic-era decoupling was short-lived. Carbon dioxide emissions per capita declined in 2020 but increased continuously from 2021 to 2024, surpassing the pre-pandemic level. Tapio elasticity indicates a shift from recessive decoupling during the pandemic shock to expansive negative and strong negative decoupling during recovery. Exploratory correlations suggest that emission changes were more strongly associated with trade balance and government expenditure than with gross domestic product growth alone. The decomposition indicates that worsening carbon intensity contributed more to the emission rebound than scale effects.ImplicationsThe results imply that economic recovery without green conditionality can reinforce carbon-intensive development. Islamic economics strengthens this implication by emphasizing stewardship, public welfare, balance, justice, and harm prevention in fiscal and trade policy.Originality/NoveltyThis study contributes by linking Indonesia’s post-pandemic decoupling analysis with fiscal policy, trade dynamics, and Islamic economic ethics, offering a policy-oriented framework for maqasid-based green recovery.